Selenium ruby lead-free high refractive index glass prepared from local sand - P. Dararutana (2018)
Most of high refractive index glasses are lead containing glasses. Because of its toxicity and considering the environmental issues as well as the human beings, lead becomes less favorable for utilization in glass production and lead free or leadless glasses have been produced by using other elements such as barium (Ba) and bismuth (Bi) to replace lead. In this work, the colorless lead-free high refractive index glasses were prepared in the laboratory scale, using the main compositions of local sand from Tak site and barium carbonate that used for replacing lead oxide. Prior to melt, selenium powder (Se) and cadmium sulfide (CdS) can be added in order to produce red colored glasses. Well-mixed and dried powders mixtures were melted in a ceramic crucible, in an electric furnace, at temperature about 1250 °C for 4 hr and primary glasses were yielded after cooling down. The physical and optical properties of the transparent and bubbles-free glass samples were measured. It was found that the density and the refractive index were increased as the increase of the concentration of Se and CdS. It was also found that the red colored glass could be obtained with the doping ratio of Se and CdS was 8:1. The modification and the morphology of glass structure were also studied.